2017
DOI: 10.20897/jisem.201704
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Framework based on Critical Success Factors for E-Commerce

Abstract: E-commerce has been increasingly applied as it promotes economic growth by enabling online shops to compete within a global market scenario. There are critical success factors that permit to distinguish a good business on the Internet and this knowledge may allow reaching an important competitive advantage for business sustainability. As many disciplines are involved, when determining critical success factors, ecommerce requires an effective coordination and integration in a collaborative way. In e-commerce, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
9
0
3
Order By: Relevance
“…Any impact that threatens to violate the autonomy of the masses is absorbed, distorted and dispersed. Therefore, it is simply necessary that the ideological impact is continuous and has an easily digestible form (Agara, 2017;Kord et al, 2017;Varela et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Any impact that threatens to violate the autonomy of the masses is absorbed, distorted and dispersed. Therefore, it is simply necessary that the ideological impact is continuous and has an easily digestible form (Agara, 2017;Kord et al, 2017;Varela et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The methods of "measuring" the success of e-commerce are different from the methods of analyzing the success of the physical services market. Therefore, the quality of e-services is defined as the overall customer satisfaction with the quality of services in the virtual market (Varela et al, 2017). In the literature (Varela et al, 2017; see Kawasaki, 2004), the prevailing view is that website design / platform design, performance, reliability (security and privacy policy), and speed of customer service are determinants of customer loyalty.…”
Section: The Success Factors For E-commercementioning
confidence: 99%
“…Therefore, the quality of e-services is defined as the overall customer satisfaction with the quality of services in the virtual market (Varela et al, 2017). In the literature (Varela et al, 2017; see Kawasaki, 2004), the prevailing view is that website design / platform design, performance, reliability (security and privacy policy), and speed of customer service are determinants of customer loyalty. It was also found that factors (eg: smooth operation of IS programs, employees who know their profession, security in virtual space, effective communication in the network) related to the efficient use of information systems ensure the successful implementation of e-commerce project ( Choshin ir Ghaffari, 2017, žr.…”
Section: The Success Factors For E-commercementioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, there are many factors that determine trustworthiness, in other words, perceptive factors preceding trust, which, depending on the trustee's context and nature, may undermine or strengthen trust. In the case of online trust, there are several attempts to identify and systematise those determining factors (Aiken et al, 2007;Amoroso & Hunsinger, 2009;Kim & Peterson, 2017;Varela et al, 2017;Wang & Emurian, 2005), making it difficult to conduct an exhaustive inventory here. However, it is worth mentioning the importance that the perception of some specific factors can have in the decision to purchase online: the perception of the value of the loss risked, of security conditions, of the website design and visual, of the business or website reputation, of previous consumer experience, etc.…”
Section: Online Trust Expectation or Website Trustworthiness Perception?mentioning
confidence: 99%